1997
DOI: 10.1111/j.1365-2842.1997.tb00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of dentine after Nd:YAG laser treatment: an in vitro study

Abstract: The purpose of this investigation was to determine the effects of Nd:YAG laser treatment on the permeability of dentine. Forty dentine discs were prepared by horizontal sectioning through the middle coronal third of freshly extracted non-carious third molars. After the removal of the pulp the discs were finished w^ith 600 grit and divided into three test groups and one control group (« = 10). For the test groups three different laser power settings were chosen: test group A: 3 X 60 sec, 60 mJ; test group B: 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
12

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
1
4
0
12
Order By: Relevance
“…15 These observations can be related to the increase of hardness demonstrated in this study. 15 These observations can be related to the increase of hardness demonstrated in this study.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…15 These observations can be related to the increase of hardness demonstrated in this study. 15 These observations can be related to the increase of hardness demonstrated in this study.…”
Section: Discussionsupporting
confidence: 66%
“…Schaller et al 15 reported that treatment with Nd: YAG would influence dentin permeability leading to an increase in superficial acid resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 6-month study by Schwartz et al (122) also compared the desensitizing effects of a Er : YAG (erbium-doped, yttrium, aluminum, and garnet) laser with a Dentin Protector s (Ivoclar Vivadent, Ellwangen, Germany) desensitizing system and reported that the laser treatment was significantly more effective in reducing DH/RDS over the study period than the Dentin Protector s . Further research is, however, required before this technique can be recognized as an acceptable treatment for this condition; indeed, several investigators (124,125) have noted safety concerns that due to the apparent destruction of the dentine surface, lasers such as the neodymium-yttrium, aluminum garnet (Nd-YAG) at moderate or therapeutic power levels may be inappropriate for the treatment of DH/RDS. Recently, a light-cured resin-based sealer was evaluated following flap surgery and was observed to reduce RDS over a 30-day period (38).…”
Section: Management Of Dh/rdsmentioning
confidence: 99%
“…Os procedimentos adesivos agem oclusivamente pela impregnação das resinas fluidas 31,49,50,69,100,101,104,152,153,162,219,251,254,271,281,286 , ou dos primers 49,51,104,240,254,271 e, ainda, das restaurações com resinas compostas 67,210,211 e com cimento de ionômero de vidro 23,40,223,45 . A luz laser também é capaz de tratar a dentina hiperestésica através da deposição de partículas 74,117,136,147,151,199,230,273,274,287 .…”
Section: Introductionunclassified